Real world design and implementation of pathfinding sewer inspection robot using a-star algorithm - Atyanta Rumaksari; Adri Gabriel Sooai; Gloria Song Abimanyu; Gunawan Dewantoro; Hartanto Kusuma Wardana; Budihardja Murtianta; Lukas Bambang Setyawan (Institute of Computer Science (IOCS), 2023)
This paper presents the design and implementation of a sewer inspection robot that utilizes the A-Star algorithm for pathfinding. The robot is intended to provide a more efficient solution for culvert workers in inspecting sewer pipes, particularly in hard-to-reach areas. The A-Star algorithm was chosen due to its ease of implementation and low computational resource requirements, making it suitable for real-time applications. The robot was designed with a modular approach, allowing for flexibility in adapting to different pipe sizes and configurations. It is equipped with various sensors and cameras, allowing for accurate inspection of pipe conditions and identification of potential issues. The A-Star algorithm was used to plan the robot's path through the sewer pipes, minimizing the time required for inspection and reducing the risk of damage to the pipes. The results of the implementation showed that the sewer inspection robot using the A-Star algorithm was able to efficiently navigate through the sewer pipes, reducing the time required for inspection and minimizing the need for manual labor. In order to check the performance, we performed experiments on six test models through simulation. On average, the proposed algorithm showed remarkable results, where all models can generate path planning to find the target from the start position. We obtained an average time completion from Models 1 to 6 with a maximum travel distance of 30 meters of 12.96, 4.47, 18.59, 20.71, 24.93, and 19.34 seconds.